Food packaging and preservation - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Handbook of food bioengineering ;, 2018)
This book explores recent approaches to preserving and prolonging safe use of food products, including packaging techniques and materials. -- Resumé vydavatele